The role of contingent self‐worth in the relation between victimization and internalizing problems in adolescents. Issue 3 (11th March 2013) - Ghoul, Assia; Niwa, Erika Y.; Boxer, Paul
ABSTRACT: Peer victimization can challenge mental health, yet limited research has considered contingent self‐worth as a moderator of that relation. This study examined the relation of peer victimization to major depressive disorder, generalized anxiety disorder, and social phobia during adolescence, and contingent self‐worth as a hypothesized moderator of those relations. Self‐report data from adolescents ( N = 716; M age = 15.95; 94% ethnic/racial minority; 63% female) illustrated that peer victimization and contingent self‐worth had significant additive effects on internalizing problems. Moderation analyses suggested that higher levels of contingent self‐worth amplify the effect of victimization on internalizing problems. For social phobia, this effect appeared to be salient only for boys. Peer victimization and bullying are receiving increased national attention and these results underscore the impact of victimization on adolescent mental health. However, interventions targeting self‐worth as a possible protective factor should be cautious not to over‐emphasize externalities in the maintenance of self‐worth.